Potassium Channel Protein KCNK6 Promotes Breast Cancer Cell Proliferation, Invasion, and Migration - Hou, Xiangchan; Tang, Le; Li, Xiayu; Xiong, Fang; Mo, Yongzhen; Jiang, Xianjie; Deng, Xiangying; Peng, Miao; Wu, Pan; Zhao, Mengyao; Ouyang, Jiawei; Shi, Lei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer is the most common malignant tumor in women, and its incidence is increasing each year. To effectively treat breast cancer, it is important to identify genes involved in its occurrence and development and to exploit them as potential drug therapy targets. Here, we found that potassium channel subfamily K member 6 (KCNK6) is significantly overexpressed in breast cancer, however, its function in tumors has not been reported. We further verified that KCNK6 expression is upregulated in breast cancer biopsies. Moreover, overexpressed KCNK6 was found to enhance the proliferation, invasion, and migration ability of breast cancer cells. These effects may occur by weakening cell adhesion and reducing cell hardness, thus affecting the malignant phenotype of breast cancer cells. Our study confirmed, for the first time, that increased KCNK6 expression in breast cancer cells may promote their proliferation, invasion, and migration. Moreover, considering that ion channels serve as therapeutic targets for many small molecular drugs in clinical treatment, targeting KCNK6 may represent a novel strategy for breast cancer therapies. Hence, the results of this study provide a theoretical basis for KCNK6 to become a potential molecular target for breast cancer treatment in the future.